Strategi Pemasaran Flash Sale Live Shopping Tiktok Shop Terhadap Minat Konsumen Dalam Membeli Produk Maybelline - Erwin Permana; Almeyra Azarine Hadityaputri; Firza Intania Azzahra; Syamsurizal Syamsurizal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The development of digital marketing has given birth to various marketing innovations that were previously unknown. One form of digital marketing innovation currently is Flash Shale Live Shopping on Tiktok. This research aims to analyze the Tiktok Shop Flash Sale Live Shopping marketing strategy on consumer buying interest in Maybelline products. The research was carried out using a descriptive qualitative approach, research data came from search results in various digital databases. The research results show that Live shopping on the TikTok Shop has proven effective in influencing consumer buying interest in Maybelline products. This success was driven by several factors: 1). Live shopping videos that display products in real time and attractive visualizations. 2). Prices during the duration of live shopping. Maybelline provides several promotions such as Buy 1 Get 1 and discount voucher promos. 3). Time, the Maybelline brand carries out live shopping for 24 hours so that it can always connect and interact with consumers such as product question and answer sessions in the comments column. 4). Maybelline products display single and bundled products at more economical prices when live shopping. The fifth factor is flash sales, the Maybelline brand uses a flash sale marketing strategy to provide big discounts for a limited time. With the live shopping marketing strategy, it also makes it easier for the Maybelline brand to meet consumer buying interest indicators, namely attention, interest, desire and action, that is, buyers can be interested and immediately buy products in live shopping sessions.